Taking a look to promoting health and complications' prevention: differences by context - Rosa Maria de Albuquerque Freire; Maria José Lumini Landeiro; Maria Manuela Ferreira Pereira da Silva Martins; Teresa Martins; Heloísa Helena Ciqueto Peres
ABSTRACT Objectives: to acknowledge and compare the health promotion and complications' prevention practices performed by nurses working in hospital and primary health care contexts. Methods: descriptive, exploratory and crosscutting study, performed with 474 nurses selected by convenience sampling. It was used a form that encompassed two categories of descriptive statements about quality in the professional exercise of nurses. This study had ethical committee approval. Results: the nurses' population was mainly women (87,3%) with an average age of 35,5 years. There was more practices of the hospital's nurses related to the identification of potential problems of the patient (p=0.001) and supervision of the activities that put in place the nursing interventions and the activities that they delegate (p=0.003). Conclusion: the nurses perform health promotion and complications' prevention activities, however not in a systematic fashion and professional practices differ by context. This study is relevant as it may promote the critical consciousness of the nurses about the need of stressing quality practices.